Control of Liquid Sloshing Container Using Active Force Control Method - Didik Setyo Purnomo; Adnan Rachmad Anom Besari; Zaqiatud Darojah (IAES Indonesia Section, 2016)
This paper presents a robust control method to relieve the sloshing of liquid container transport using Active Force Control (AFC) method. A model of two degree-of- freedom (2-DOF) liquid container transfer was implemented in this research as the main dynamical system to be controlled. The surface of liquid is maintained in a flat position, so that changes the slope of liquid surface countered by changing the acceleration of container. The focus of this research is how to use AFC method being applied to the system, so that it can suppress liquid sloshing. The control scheme were simulated, compare between PID-AFC and pure PID. Simulations has been conducted, the results show that the PID-AFC have superior performance to suppress the sloshing compared with pure PID, especially if disturbance occurred.